Transfusion-free interval is associated with improved survival in patients with higher-risk myelodysplastic syndromes engaged in routine care. Issue 1 (2nd January 2019) - Bell, Jill A.; Galaznik, Aaron; Blazer, Marlo; Farrelly, Eileen; Ogbonnaya, Augustina; Raju, Aditya; Eaddy, Michael; Fram, Robert J.; Faller, Douglas V.
Abstract: Most higher-risk myelodysplastic syndrome (HR-MDS) patients will become transfusion-dependent, leading to potential complications, including infections or end-organ dysfunction. Data correlating achievement of transfusion-free intervals (TFIs) during first-line therapy (1LT) with survival are sparse. We evaluated HR-MDS patients receiving 1LT diagnosed from 1/1/2008 to 7/31/2015 and the impact of a TFI (≥60-day interval without transfusions) on progression-free and overall survival (PFS, OS) using Cox proportional-hazard models. Two hundred and twenty-nine HR-MDS patients received 1LT; overall, median PFS/OS were 8.4 months and 14.7 months, respectively. Two-year PFS/OS were 22.3% and 34.6%, respectively. Median PFS/OS were longer for patients with vs. without a TFI (16.9 vs. 6.1 months and 26.1 vs. 11.8 months, respectively; p < .01 [both]). Two-year PFS (43.0% vs. 3.9%; p < .01) and 2-year OS (51.8% vs. 22.5%; p < .01) were also longer in patients with a TFI vs. not. Achievement of a TFI during 1LT appears to positively affect PFS and OS in HR-MDS patients.